1990
DOI: 10.1515/hfsg.1990.44.5.347
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry of Lignin III. Mechanochemical Reactions of β—O—4 Lignin Model Compounds

Abstract: Mechanochemical reactions of ß-O-4 units of Hgnin were discussed on the basis of thc rcsults from veratryl glycerol-ß-guaiacyl (I) and vanillin (II) ethers and relatcd compounds, which wcrc trcatcd with ceramic ball mill for l hr in air. The homolytic cleavage of aryl cthcr bonds was obscrvcd only in thc compounds containing para -carbonyl group. In particular, the cleavage of Cß-O bond in compound (II) gave vanillin with 18.8% yield.This was followed by the homolytic cleavage of Ca-Cß to givc 3 and 4 and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 5 publications
(6 reference statements)
0
17
0
Order By: Relevance
“…Many efforts have been made to understand that the ball milling destroys the side-chain structure of lignin by the cleavage of ␤ O 4 bond and increases ␣-carbonyl group in a certain degree (Lu and Ralph, 2010). Lee and Sumimoto (1990) found that the structural changes of lignin during the milling process caused via a free radical mechanism, and the produced radicals might initiate further degradation. Fujimoto et al (2005) suggested that regardless of the conditions used, ball milling changes the structure of lignin via ␤ O 4 cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to understand that the ball milling destroys the side-chain structure of lignin by the cleavage of ␤ O 4 bond and increases ␣-carbonyl group in a certain degree (Lu and Ralph, 2010). Lee and Sumimoto (1990) found that the structural changes of lignin during the milling process caused via a free radical mechanism, and the produced radicals might initiate further degradation. Fujimoto et al (2005) suggested that regardless of the conditions used, ball milling changes the structure of lignin via ␤ O 4 cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin is modified e.g. by hydrolytic cleavage of ether bonds and by homolytic cleavage of covalent bonds (Hon 1983, Lee & Sumimoto 1990, resulting in the generation of low molecular weight lignin fragments and relocation of lignin from inner cell wall layers to the fibre surface (Zavarin 1984, Widsten et al 2001. Homolytic cleavage of β-O-4 ether bonds in fibre lignin generates phenoxy radicals that may undergo various further chemical reactions affecting i. the molecular size distribution and content of functional groups of the lignin polymers and ii.…”
Section: Enzymes In Lignin Activationmentioning
confidence: 99%
“…Homolytic cleavage of β-O-4 ether bonds in fibre lignin generates phenoxy radicals that may undergo various further chemical reactions affecting i. the molecular size distribution and content of functional groups of the lignin polymers and ii. the generation of water extractable material enriched in hemicellulose and aromatic substances of lower degree of etherification and richer in phenolic hydroxyl groups (Lee & Sumimoto 1990, Widsten et al 2001. Hardwood lignins with high syringyl content (see Chapter 7 of this book for discussion of chemical compositions of lignins) have a lower Tg as compared to other lignins (Olsson & Salmen 1992).…”
Section: Enzymes In Lignin Activationmentioning
confidence: 99%
“…Lee and Sumimoto (4) reported that the treatment of veratrylglycerol-(3-guaiacyl ether with a ceramic ball mill (CBM) gave almost no reaction product, but veratrylglycerol-Q-vanillin ether furnished about 18.8% of vanillin, a p-carbonyl phenol, and others. When phenylcoumaran derivatives (5,6) having an aldehyde group on it's B-ring were treated with a CBM, a vibration ball mill (VBM) or a laboratory refiner, a few percents of stilbenes having a p-carbonyl phenol structure (14) , condensation reaction of compound (6) with ethyl 2-methoxyphenoxy acetate (7) yielded the condensation product (8), which was reduced with lithium aluminum hydride to give compound (9).…”
Section: Introductionmentioning
confidence: 99%